Modifiable risk factors and the development of psoriatic arthritis in people with psoriasis. (2nd September 2019) - Green, A.; Shaddick, G.; Charlton, R.; Snowball, J.; Nightingale, A.; Smith, C.; Tillett, W.; McHugh, N.; ,
Summary: Background: Psoriatic arthritis (PsA) is a progressive and often destructive joint disease affecting approximately 20% of people with psoriasis. Objectives: To investigate associations between obesity, changes in body mass index (BMI), alcohol intake and smoking status and the development of PsA in people with psoriasis. Methods: We undertook a cohort study involving incident cases of psoriasis identified from the U.K. Clinical Practice Research Datalink between 1998 and 2014. The associations between smoking, alcohol and BMI and development of PsA were assessed using generalized additive models. Additionally, the risks associated with a change in BMI during follow‐up were investigated using distributed lag nonlinear models. Results: We identified 90 189 incident cases of psoriasis (42% male, mean age 51 years), of whom 1409 had a subsequent record of PsA diagnosis. BMIs of 25·0–29·9, 30·0–34·9 and ≥ 35·0 kg m −2 were significantly associated with an increased risk of developing PsA compared with BMIs < 25·0 kg m −2 : adjusted odds ratios (95% confidence intervals) 1·79 (1·46–2·19), 2·10 (1·67–2·63) and 2·68 (2·09–3·43), respectively. Reducing BMI over a 10‐year period (linearly) was associated with a reduction in the risk of developing PsA compared with BMI remaining constant over the same period. Increased risks of developing PsA were associated with moderate drinking but not with former or heavy drinking or with current or past smoking status. Conclusions: In this incident psoriasis cohort, increased BMI and moderate drinking, but not heavy drinking or smoking status, were associated with an increased risk of PsA in people with psoriasis. Importantly, we have shown that reducing weight may result in a reduction in the risk of developing PsA. What's already known about this topic? There is some evidence that increased body mass index is associated with an increased risk of developing psoriatic arthritis. There are conflicting results surrounding the relationship between smoking and the development of psoriatic arthritis among patients with psoriasis. What does this study add? Using a nonlinear and lagged effect of body mass index measured over time we have shown that reducing body mass index may be associated with a reduction in the risk of developing psoriatic arthritis. We have found no evidence that smoking alters the risk of developing psoriatic arthritis in patients with psoriasis. Abstract : Linked Editorial: Ogdie and Eder. Br J Dermatol 2020; 182 :523–524 . Plain language summary available online